Molecular modeling approaches in formulations of sunscreen nanoemulsion with active ingredients asiaticoside from Centella asiatica (L) urban fraction - Rini Dwiastuti, Valentina Putri Embun Kinanti, Immanuela Putri Maharani Estyaningrum, Agustina Setiawati, Rifki Febriansah, Sri Hartati Yuliani, Stephanus Satria Wira Waskitha, Lutfi Chabib (Journal of Applied Pharmaceutical Science, 2025)
In silico molecular modeling can be used to incorporate active pharmaceutical ingredients in drug delivery systems. This study used asiaticoside as the active pharmaceutical ingredient in a nanoemulsion with olive oil as a penetration enhancer. Asiaticosides have potential as sunscreen agents. This study aimed to determine the correlation between computational and experimental research on nanoemulsion formation. Computational or in silico modeling was performed using molecular dynamics (MD) simulations followed by short-range van der Waals and Coulomb energy calculations to understand the dynamic energy changes in the nanoemulsion assembly and the morphology formed. The empirical experiment was conducted by formulating the nanoemulsion as suggested by in silico modeling, followed by the determination of its particle size and shape. The experimental results indicated that the nanoemulsion particles formed a monodisperse system, with particle sizes in the nanometer range. The particles appeared spherical with smooth surfaces and exhibited no aggregation or separation in the nanoemulsion system. These results were also well correlated with the in silico modeling studies, showing that the nanoemulsion formed during the initial production run of 250-ns MD simulations and maintained stability throughout the simulations.
Keywords: Asiaticoside, formulation, molecular modeling, nanoemulsion, MD simulations